Dynamics Of Economic Growth And Quality Of Human Resources In The Archipelago North Maluku Province - Abae, Irawan; Ahmad, Abdul Chalid; Hasyim, Aziz (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2024)
This study examines the relationship between the Gross Regional Domestic Product (GRDP) and the Human Development Index (HDI) in North Maluku Province. The research aims to analyze the influence of HDI, Government Expenditure, Investment, and Labor Force on Economic Growth and the impact of life expectancy, school life expectancy, and per capita expenditure on HDI. The study employs the Two Stage Least Square analysis method using panel data processed through the Eviews application. The results indicate that the HDI, Government Expenditure, and Investment variables significantly affect GRDP, while the Labor Force variable is optional. Meanwhile, the GRDP variable does not substantially affect HDI, but the Life Expectancy, School Life Expectancy, and Per Capita Expenditurea variables significantly impact HDI. The conclusion suggests that economic growth does not necessarily guarantee an improvement in the quality of human resources in North Maluku. The study recommends including additional variables related to GRDP and HDI to better understand their impact in each region.